Fundamentals of dental jurisprudence, ethics and practice management - Bellosillo, Josue N.; Tripon- Rosero, Leonor M. ;Mapili, Emmanuel LJ (Quezon City, Philippines : Central Book Supply, 2009)
Written to provide dental students and practitioners with an organized and manageable format covering the essential components of legal, ethical and management issues concerning dentists and to make their learning and teaching easier.
Part I. Dental law and related legislations -- Part II. Legal Responsibilities of dentist -- Part III. Ethical and moral responsibilities of dentists -- Part IV. Dental practices management.
Includes bibliographical references and index.
Keywords: DENTAL JURISPRUDENCE